KEMATIAN SEL TERPROGRAM (APOPTOSIS) - Yanti Fitri Yasa (Yayasan Nusantara Hasana Berdikari, 2026)
Apoptosis is a programmed cell death mechanism that plays a crucial role in maintaining cellular homeostasis, tissue development, and eliminating damaged cells. Disruption of apoptosis regulation is known to contribute to various diseases, such as cancer and neurodegenerative disorders. Therefore, studying the mechanisms of apoptosis is crucial to strengthen our biological understanding and its clinical implications. This study employed a descriptive-analytical literature review approach. Data were obtained from international scientific articles published in reputable databases and analyzed qualitatively to examine the molecular mechanisms, apoptosis pathways, and the role of key regulators in programmed cell death. The results indicate that apoptosis proceeds through two main pathways: the intrinsic pathway involving mitochondria and the release of pro-apoptotic factors, and the extrinsic pathway triggered by the activation of death receptors. Both pathways culminate in the activation of caspases, the primary executors of apoptosis. Furthermore, additional regulatory mechanisms were identified that refine the classical apoptosis model. Apoptosis is a highly controlled and integrated biological process, playing a crucial role in the balance and continuity of cellular function. A comprehensive understanding of the mechanisms of apoptosis provides a crucial contribution to the development of therapeutic approaches based on the regulation of programmed cell death.